ANALISIS HUBUNGAN PANJANG BERAT DAN FAKTOR KONDISI IKAN TEMPAKUL (Periopthalmus barbarus) DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) KOTA TARAKAN - Gazali, Salim; Firdaus, Muhammad; Heriyana, Heriyana (Jurnal Harpodon Borneo, 2019)
Conservation Mangrove and Bekantan Bakantan Mangrove conservation territory in Tarakan East Borneo built as located bakantan conservation and mangrove Education. For more manage grown as tourism destination. Purpose of this research know it analysist relationship between length and weight, and than conditions index of tempakul fishes (Periopthalmus barbarus) at Conservation mangrove and bekantan in Tarakan City. Researched as long as three months, on September to Desember 2018. This research used descriftif method from research founded tempakul tempakul fishes male and female. Negative allometric performel in factor of condition of tempakul fishes it?s about 0,01-0,49 it showed that bodies of the fishes wash very slim